Progress in blood transfusion for liver transplantation - YU Xiaochao; XU Ronghua (Zhongguo shuxue zazhi, 2025)
Liver transplantation provides a life-saving option for patients with end-stage liver disease. Although blood transfusion remains essential in most liver transplan tprocedures, it carries risks of severe complications, including organ failure and mortality. Recent advances have elucidated the complex relationships among transfusion indications, microscopic characteristics of hematology, and adverse reactions. This review synthesizes the latest research progress in blood transfusion in liver transplantation, offering evidence-based strategies for blood transfusion in liver transplantation.